Frequência da Síndrome de Meares-Irlen entre alunos com dificuldades de leitura observadas no contexto escolar - Laura Nequini de Faria (2011)
The Meares-Irlen Syndrome (MIS) is characterized by symptoms of visual stress and visual perceptual distortions, which often leads to impairment of reading ability. This condition, however, is minimized or eliminated with the use of transparencies (sheets of transparent plastic that are placed on the page). Studies show that the prevalence rates of MIS are high and vary between 12.5 to 20%. As in Brazil there are no records of these estimates, this study aimed to investigate the frequency of occurrence of MIS in students of elementary school, from a public school. The research was divided into five stages, and the first stage the teachers answered a questionnaire about reading from each of the students, then the teachers indicated those students who they thought had reading difficulties. The students nominated by the teachers, after the parents had authorized and signed the consent form, underwent then were evaluated for MIS using the method proposed by Irlen (1987) a routine ophthalmologic examination. Once students with MIS were identified, we asked the teachers to indicate those students who they thought had regular reading. So, two groups were formed, the clinical group (CG) composed of students with MIS and non clinical group (NCG) consisting of students, without complaints of reading difficulties. Students in the CG were then subjected to a computerized reading test without and then with transparency sheets (overlays). These data were then compared. Then the NCG was subjected to the same computerized reading assessment. The data from the CG were then compared to the NCG group. The results indicated that the frequency of occurrence of the MIS is high and it is consistent with findings in the literature. And that when individuals with MIS use transparencies(overlays), eye movement parameters and reading speed improved significantly and are equal to the standard presented by NCG.